2020
DOI: 10.24109/2176-6681.rbep.101i259.4610
|View full text |Cite
|
Sign up to set email alerts
|

Educación superior y universidad en América Latina: perspectivas temáticas para debates e investigaciones

Abstract: Educação superior e universidade são temas de amplo interesse no mundo todo e reúnem esforços de múltiplos agentes e disciplinas. Com base nas configurações do campo da educação superior e nos debates da Cátedra Unesco Universidad e Integración Regional, este artigo analisa os temas emergentes na América Latina, com ênfase nas realidades nacionais da Argentina, do México e do Brasil. Com abordagem ensaística, discute os temas relevantes para os três países e aponta os desafios para o debate político e para a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Dispone en las Instituciones Federales de Educación Superior la reserva de cupo mínimo de 50% de las vacantes para alumnos/as provenientes de escuelas públicas. Y a la vez, dentro de ese grupo, establece una "subcuota" para alumnos/as negros/as, pardos/as, indígenas y personas con discapacidad (Caregnato, Santin, Del Valle y Didrikson, 2020).…”
Section: Principales Políticas Para La Democratización Del Ingreso En...unclassified
“…Dispone en las Instituciones Federales de Educación Superior la reserva de cupo mínimo de 50% de las vacantes para alumnos/as provenientes de escuelas públicas. Y a la vez, dentro de ese grupo, establece una "subcuota" para alumnos/as negros/as, pardos/as, indígenas y personas con discapacidad (Caregnato, Santin, Del Valle y Didrikson, 2020).…”
Section: Principales Políticas Para La Democratización Del Ingreso En...unclassified
“…When turning to Mexico, it is found that outside attracting international talent, there is a will to universalise higher education as the current context precludes equal opportunities for citizens to access this training. The pervasive wealth disparities within the population reproduces systems of inequity and sets higher education, even with partial funding, as an impossibility for a vast proportion of individuals, a fact at the forefront of this movement toward greater inclusion (Caregnato et al, 2021). Both Mexico and Brazil, as such, have implemented affirmative action to facilitate their indigenous population's access to higher education, pointing to a positive shift in previously held financial priorities over the diversification of their scholars and the richness of the cultural contribution of indigenous researchers (Oyarzún, Franco and McCowan, 2017).…”
Section: Latin Americamentioning
confidence: 99%